Rhodobacter sphaeroides as a model to study the ecotoxicity of 1-alkyl-3-methylimidazolium bromide - Liu, Xiao-Lin; Chen, Ming-Qing; Jiang, Yang-Lin; Gao, Rong-Yao; Wang, Ze-Jun; Wang, Peng (Frontiers in Molecular Biosciences, 2023)
The purple non-sulfur bacterium Rhodobacter sphaeroides was selected as a biological model to investigate its response to the toxicity of 1-alkyl-3-methylimidazolium bromide ([Cnmim]Br), a type of ionic liquid (IL), with different alkyl chain lengths (n describes the number of carbon atoms in the alkyl chain). The inhibition of bacterial growth by [Cnmim]Br was positively correlated with n. Morphological characterization revealed that [Cnmim]Br caused cell membrane perforation. The signal amplitude of the electrochromic absorption band shift of endogenous carotenoids showed a negatively linear correlation with n, and the amplitude of the blue-shift of the B850 band in light-harvesting complex 2 showed a positively linear correlation with n. Furthermore, an increase in blocked ATP synthesis and increase in antioxidant enzyme activity were observed in chromatophores treated with ILs containing longer alkyl chains. In summary, the purple bacterium can be developed as a model to monitor ecotoxicity and examine the mechanism of IL toxicity.